PENGARUH KEGIATAN BERKEBUN TERHADAP KECERDASAN NATURALISTIK ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 KOTA PEKANBARU - Nadia Nadia; Devi Risma; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to find out about gardening activities on naturalistic intelligence of children aged 5-6 years old at TK Negeri Pembina 1 Pekanbaru City. The population in this aged 5-6 years old at TK Negeri Pembina 1 Pekanbaru City. The sample in this research is the group b amounted to 19 children, consists of 11 women and 9 men. Data collection used in this study was by pretest and posttest observation. The data analysis technique in this study used the t tset using SPSS version 20. This research was an experimental study using the design of one group pretest posttest design. Based on the analysis of the data and the results of percentages on a significant effect, it can be seen from the results of the pretest (before treatment) abtained a value of 190 with an average 0f 10. Then do the experiment using gardening activities, so that the posstest obtained 301 values with an average of 15,84. The find out how much the effect gerdening activities on naturalistic intelegence of children aged 5-6 years old at TK Negeri Pembina 1 Pekanbaru City was 58,42% and 41,58% was influenced by other factor.Key Words: Gardening activities, naturalistic intelegence